2017
DOI: 10.1111/aogs.13140
|View full text |Cite
|
Sign up to set email alerts
|

Patient selection for later delivery timing with suspected previa‐accreta

Abstract: Patients with suspected previa-accreta and no risk factors for preterm birth are at low risk for an unscheduled delivery prior to 36 weeks. Those with no concern for percreta or increta or no prior cesarean section may also be candidates for later delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…For 52 women (26.3%) in our study population, gestational age at the time of delivery was ≥ 37 weeks, which had no significant association with blood loss and/or post operative complications. It seems that this finding is in association with the recent publications that suggested physicians can decide case by case for PAS termination and it is not necessary to terminate all cases at the 34 weeks’ of gestation [ 28 ].…”
Section: Discussionsupporting
confidence: 76%
“…For 52 women (26.3%) in our study population, gestational age at the time of delivery was ≥ 37 weeks, which had no significant association with blood loss and/or post operative complications. It seems that this finding is in association with the recent publications that suggested physicians can decide case by case for PAS termination and it is not necessary to terminate all cases at the 34 weeks’ of gestation [ 28 ].…”
Section: Discussionsupporting
confidence: 76%
“…The third study of 84 women who had reached 34 +0 weeks of gestation with a suspected praevia accreta found that those with no risk factors for preterm birth are at low risk for an unscheduled delivery prior to 36 weeks of gestation. 170 Evidence level 2+…”
Section: 4mentioning
confidence: 99%
“…Similarly, Rac et al found that emergency delivery for bleeding decreased significantly with advancing pregnancy, 71% of the cases delivered at 36 weeks of gestation and beyond, and more than 90% of the cases had no bleeding complications 36 . Perlman et al evaluated PAS cases by classifying them according to preterm delivery risk factors and found that cases without preterm delivery risk had a low risk of unplanned delivery before 36 weeks of gestation 37 . In 2018, RCOG reported that planned delivery at 35+0 to 36+6 gestational weeks provides the best balance between fetal maturity and the risk of unplanned delivery in PAS cases without risk factors for preterm delivery 15 .…”
Section: Discussionmentioning
confidence: 99%